Use Of HbA 1 C In The Diagnosis of Diabetes mellitus Type 2 In High Risk Patient Attending Outpatient Clinic (KRK)HUSM - Adibah Hanim, Ismail@ Daud (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2008)
Introduction : For many years diagnosis of diabetes mellitus has dependent primarily on results of OGTT. Fasting hyperglycaemia, a late manifestation of diabetes is not generally useful for evaluating the presence or severity of glucose tolerance. OGTT for the diagnosis of diabetes is inconvenient and require a great deal of patient cooperation. It is known to be poorly reproducible and is often not performed. To improve patient compliance with testing, use ofHbA1c to diagnose diabetes has been suggested. Objectives : To evaluate the use of HbA1c as a diagnostic test for diabetes in high risk groups attending Klinik Rawatan Keluarga, HUSM. It is also to determine the sensitivity and specificity of HbA1c as compared to FPG and OGTT to diagnose type 2 diabetes and the optimal cutoff point of HbA 1 c for the diagnosis of type 2 diabetes. Methodology : This was a cross sectional study conducted from March 2005 to January 2006. Patient age 35 years and above with one or more risk factors for type 2 diabetes which includes BMI 2: 23, hypertension, history of GDM or big baby (2: 4.0 kg), family history of diabetes in first degree relatives, hyperlipidaemia and dyslipidaemia, who consented for the study were included. OGTT and HbAlc were performed in 402 asymptomatic high-risk subjects with positive screen using capillary blood glucose ~ 5.6mmol/l. Data was analyzed using SPSS version 11.5. Result :The mean age and BMI for study samples were 51.6 ±_9.2 and 26.8 ±._ 4.8 respectively. The mean FPG level was 5.6 ± 2.2mmo/l, mean 2h-PP level was 9.6 ± 5.3mmol/l and mean HbA1c was 6.0 ±1.5%. Of 402 patients, 45.3% (n = 182), was diagnosed as normal glucose tolerance, 22.6% (n = 91) had impaired glucose tolerance or impaired fasting glucose and 32.1% (n = 129) had diabetes mellitus. Patients with abnormal glucose tolerance had a higher percentage of HbA 1 c than subjects with normal glucose tolerance (p< 0.001). HbA1c of 7.0% gave an optimal sensitivity of 81% and specificity of 91% to predict a FPG of 7.0mmo/l. Whereas; HbA1c of 6.4% with sensitivity and specificity of 68% and 89% respectively was an optimal value to predict 2h-PP 1l.lmmol/l. Finally, HbA1c of 6.4% gave an optimal sensitivity of 68% and specificity of90% to predict FPG 7.0mmol/l and/or 2h-PP ll.lm.mol/1. Conclusion : HbA 1 c measurement in high risk group of patients is a highly specific test and convenient alternative to fasting plasma glucose or oral glucose tolerance test for diagnosis oftype 2 diabetes.